Effect of Cryosoaking Time on Transition in Wear Mechanism of M2 Tool Steel. (24th February 2013) - Dhokey, N. B.; Dandawate, J. V.; Rawat, R.
Abstract : Specimens of M2 were hardened (H) by quenching at 1200°C, triple tempered (TTT) at 400°C, and then cryogenically (C) treated at minus 185°C for varying lengths of time interval starting from 4 hours to 48 hours of cryosoaking followed by soft tempering at 100°C to relieve cold stresses (HTC). Underlying wear mechanism, hardness, and impact energy were studied and optimum cryosoaking time was established. It was felt that wear resistance of cryogenically treated material was influenced by the so-called tertiary carbides possibly produced as a result of cryogenic treatment.